The evaluation of multiplication capacity in Galleria of entomopathogenic nematode isolates from Vietnam - Chau, Nguyen Ngoc; My, Vu Tu; Duyen, Nguyen Thi; Ehlers, Ralf-Udo (Academia Journal of Biology, 2012)
A total of 43 isolates of entomopathogenic nematodes of Vietnam were assessed on reproduction capacity in the last instar larvae of great wax moth (Galleria mellonella). The total yield of infective juveniles (IJs) on the Galleria mellonella were varied between indigenous isolates with significant different of multiplication. The amounts of IJs were produced in each Galleria from several thousands to hundreds thousands. These were shown a great difference of the reproduction capacity between indigenous isolates/species of entomopathogenic nematodes. In general, the multiplications of Steinernema isolates were lower than the multiplication of Heterorhabditis isolates. Among Steinernema isolates, however, the multiplications of some isolates were relatively low such as isolate S-DL9 (S. eapokense) with 4,378 ± 509 IJs, whereas other ones were relatively high such as S-TX1 (S. sangi) with 68,343 ± 8,942 IJs. These were also occurred significant difference between isolates within species that were particularly happened isolates of Heterorhabditis indica with average yields varieties from 18,900 IJs at H-PP16 to 233,500 ± 39,100 at H-NT3. The experiments showed the relationship between multiplication capacity of IJs and inoculation concentration and each isolate has an optimal inoculation concentration for highest multiplication. These data to be provided the important information for evaluation of potential isolates for biocontrol.